Peran Media Digital terhadap Perkembangan Pembelajaran Bahasa Arab Santri PPTQ AR-ROYYAN Pacitan - Aldi Prastiawan; Sanjaka Yekti (Jurnal Pendidikan, Bahasa dan Budaya, 2026)
This study aims to describe the role of digital media in Arabic language learning development at PPTQ Ar-Royyan Pacitan, including its implementation, challenges, and impacts. The research employed a qualitative method using semi-structured interviews and direct observation of the learning process. The participants consisted of students, university students, and teachers at PPTQ Ar-Royyan Pacitan.The findings show that digital media plays a supportive role in Arabic language learning through the use of platforms such as YouTube, the Al-Ma’ani dictionary application, e-books, and social media. These tools help students improve their understanding of learning materials, expand vocabulary mastery, and develop Arabic language skills through more engaging audio-visual presentations. Digital media also provides learning flexibility, as it can be accessed anytime and anywhere. However, several challenges were identified, including limited internet access, reduced learning concentration due to social media distractions, and decreased direct interaction between students and teachers. The study also reveals that excessive use of digital media may lead to dependency and reduce students’ motivation to study classical Islamic texts directly. Therefore, digital media is considered only as a supporting tool in pesantren education and cannot replace the traditional system that emphasizes direct interaction, moral values, and teacher role modeling. With proper supervision, digital media can effectively support Arabic language learning in Islamic boarding schools.